2002
DOI: 10.1097/00006199-200211000-00002
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Increase Safety Behaviors of Abused Women

Abstract: These findings demonstrate that an intervention to increase safety behaviors of abused women is highly effective when offered following an abusive incident and remains effective for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 15 publications
6
117
1
1
Order By: Relevance
“…Study 3: McFarlane et al, (2002) conducted a Randomized Control Trial (RCT) to determine the effectiveness of a telephone intervention promoting safety behaviours for victims of IPV. This paper utilizes two conceptual models to guide an 18-month clinical trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study 3: McFarlane et al, (2002) conducted a Randomized Control Trial (RCT) to determine the effectiveness of a telephone intervention promoting safety behaviours for victims of IPV. This paper utilizes two conceptual models to guide an 18-month clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…The first author (FL), examined the full text of these and manually searched the reference lists of these articles. Subsequently three articles (Gutman et al, 2004;Helfrich & Avileo, 2001;McFarlane et al, 2002). were retained for full review and critical analysis ( Table 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…43 Clinical staff must be well trained and receive administrative support for the time required to screen and refer patients. 43,44 Although the 2004 U.S. Preventive Services Task Force issued an ''I'' recommendation, indicating insufficient evidence for or against family violence including elder abuse and IPV, 45 a recent comprehensive review of the effectiveness of screening concluded that at least six screening tools were ''highly accurate,'' and several trials of advocacy or counseling interventions reduced IPV. 46 This review indicates that the required screening tools exist and clinical interventions do improve violence outcomes for some women.…”
Section: Discussionmentioning
confidence: 99%
“…A third advocacy study by the same research group was a randomised controlled trial, 135,136 based in a family violence unit of a large urban district attorney's office. All women received the usual services of the unit, which included processing of civil protection orders and optional advocacy referral, and the phone number of a caseworker for further assistance.…”
Section: Studies Included In Our Previous Reviewmentioning
confidence: 99%